Occupational HIV risk for health care workers: risk factor and the risk of infection in the course of professional activities - Wyżgowski P; Rosiek A; Grzela T; Leksowski K (Therapeutics and Clinical Risk Management, 2016)
Przemysław Wyżgowski,1 Anna Rosiek,2 Tomasz Grzela,1 Krzysztof Leksowski1,2 1Department of General Surgery, Military Hospital, 2Public Health Department, Faculty of Health Sciences, Nicolas Copernicus University in Toruń, Bydgoszcz, Poland Abstract: Virtually created panic among health care workers about pandemic acquired immune deficiency syndrome prompted us to review the scientific literature to investigate the risk of human immunodeficiency virus (HIV) transmission in the daily works of health care workers, especially surgeons and anesthesiologists. In this review, we report worldwide valuations of the number of HIV infections that may occur from unsafe daily work in health care. We also present how to minimize the risk of infection by taking precautions and how to utilize postexposure prophylaxis in accordance with the latest reports of the Centers for Disease Control and Prevention. HIV-infected patients will be aging, and most of them will become the candidates for procedures such as major vascular reconstruction and artery bypass grafting, where the risks of blood contact and staff injury are high. For these reasons, all health care workers need to know how to prevent, and fight following the accidental exposure to HIV. Keywords: HIV infection, risk factor, anesthesiologist, surgeons